Effects and function of citric acid on fermentation quality and microbial community in sugarcane tops silage with high and low water-soluble carbohydrate content - Qichao Gu; Jie Zhang; Bo Lin; Hao Ding; Qi Yan; Caixiang Wei; Yipei Yao; Ruizhanghui Wang; Caixia Zou (BMC Plant Biology)
Abstract Sugarcane tops silage (STS), as a source of roughage for ruminants, is rich in water-soluble carbohydrate (WSC) content, which significantly affects silage quality. Citric acid (CA) is a low-cost natural antimicrobial agent that can inhibit undesirable microbes and improve silage quality. The objectives of this study were to investigate the effects of CA on the chemical composition, fermentation quality, microbial communities, and metabolic pathways of STS with high and low WSC contents before or after aerobic exposure. Fresh sugarcane tops with low-WSC [143.05 g/kg dry matter (DM)] and high-WSC (249.99 g/kg DM) contents were treated with and without CA and then ensiled for 125 days, followed by aerobic exposure for 4, 8, and 16 days. The results showed that high-WSC STS had lower crude protein (CP) content and higher DM, neutral detergent fiber (NDF), and acid detergent fiber (ADF) contents, whether treated with CA or not. CA-inoculated silage exhibited decreased DM loss and enterobacteria (EB) counts compared to the control. High-WSC STS treated with CA had higher WSC content and lower yeast count than those without CA inoculation. During the 0–16 days of aerobic exposure, the propionic acid and butyric acid contents in CA-inoculated silage were almost unchanged and ranged from 0 to 1 g/kg DM. Meanwhile, the ethanol content was almost unchanged and ranged from 0 to 1 g/kg DM only in low-WSC STS, irrespective of CA addition. Before aerobic exposure, CA inoculation decreased the abundances of undesirable microbes (e.g., Clostridium_sensu_stricto_12 and Paecilomyces) and animal pathogens, while amino acid metabolism was lower in high-WSC STS regardless of CA treatment. After aerobic exposure, CA inoculation increased the abundance of bacteria with antibacterial effects, including Paenibacillus and Bacillus. Moreover, the metabolism of energy and nucleotides was lower in high-WSC STS treated with CA, and the animal pathogens was lower in low-WSC STS treated with CA. In conclusion, CA inoculation could be effective in decreasing nutrients loss, improving fermentation quality, inhibiting harmful microorganisms, and modulating the metabolic pathways of microorganisms in STS with high and low WSC contents prior to and after aerobic exposure.